AN APPLICATION OF SAPPÃYA 4 IN BUDDHIST TOURISM MANAGEMENT OF WAT PHRA BOROMMATHAT CHEDI KHIAN BANG KAEW, PHATTHALUNG PROVINCE - Warachoto (Thongchim), Phra Kraisorn; ., Phrakhru wijitajarn; ., Phrakru Kositwattananukul (Journal of MCU Nakhondhat, 2023)
This thesis has 3 main objectives: 1) To study the concept of Buddhist tourism management at Wat Phra Boromathat Chedi Khian Bang Kaew Phatthalung Province 2) To study the Sappãya 4 as appeared in Buddhist scriptures. 3) To apply the Sappãya 4 in Buddhist tourism management at Wat Phra Boromathat Chedi Khian Bang Kaew Phatthalung Province. It is qualitative research, focuses on document studies and in-depth interviews. The research results were found that: 1)The concept of Buddhist tourism management at Wat Phra Boromathat Chedi Khian Bang Kaew Phatthalung Province.It found that Management refers to the process of carrying out various activities to achieve goals for the utmost benefit of the people, communities, society and the nation. Buddhist tourism management of Wat Phra Boromathat Chedi Khian Bang Kaew, Phatthalung Province. There are 4 issues that should be improved, which can be summarized into 4 issues: 1) Place, 2) Food, 3) People, and 4) Dhamma. 2) The Sappãya 4 as appeared in Buddhist scriptures. It found that the Sappãya 4 is the Buddhist principle for proper management of life and activities. The Sappãya 4 consists of 1) ÃvãsaSappãya 2) ÃhãraSappãya 3) PuggalaSappãyaand 4) Dhamma Sappãya. 3) An Application of the Sappãya 4 in Buddhist tourism management at Wat Phra Boromathat Chedi Khian Bang Kaew Phatthalung Province. It found that the Sappãya 4 is a principle for proper management of life and activities by applying the ÃvãsaSappãya in order to solve the problem of location, ÃhãraSappãya to solve food problems, PuggalaSappãya to solve personal problems and Dhamma Sappãya in order to solve the Dhamma problem.